1983
DOI: 10.1099/00221287-129-3-653
|View full text |Cite
|
Sign up to set email alerts
|

The Role Of Limited Respiration In The Incomplete Oxidation Of Glucose By Saccharomyces Cerevisiae

Abstract: \The respiratory capacity of Saccharomyces cerevisiae growing in continuous culture on glucose and on mixtures of glucose and ethanol was investigated. An oxygen uptake rate of 8 mmol g-l h-l was found to limit the ability of the organism to degrade a substrate purely oxidatively. On glucose as sole energy and carbon source, this respiration rate was invariably achieved at an identical growth rate and thus at an identical substrate uptake rate when the inlet glucose concentration was varied. The rate of ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
145
3
1

Year Published

1988
1988
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(164 citation statements)
references
References 18 publications
(17 reference statements)
11
145
3
1
Order By: Relevance
“…Both fermentative and oxidative metabolic pathways co-exist (De Deken 1966;Mazzoni et al 1992) and thus we propose to classify K. laais as a short-term Crabtree-negative and a long-term Crabtree-, or Warburg-positive yeast. De Deken (1966) has suggested that the Crabtree effect is related to, or mediated by, glucose repression, while other authors have suggested that the effect is attributable to a limited capacity of the respiratory chain (Rieger et al 1983; K/ippeli and Sonnleitner 1986). Neither view is likely to be correct.…”
Section: Discussionmentioning
confidence: 99%
“…Both fermentative and oxidative metabolic pathways co-exist (De Deken 1966;Mazzoni et al 1992) and thus we propose to classify K. laais as a short-term Crabtree-negative and a long-term Crabtree-, or Warburg-positive yeast. De Deken (1966) has suggested that the Crabtree effect is related to, or mediated by, glucose repression, while other authors have suggested that the effect is attributable to a limited capacity of the respiratory chain (Rieger et al 1983; K/ippeli and Sonnleitner 1986). Neither view is likely to be correct.…”
Section: Discussionmentioning
confidence: 99%
“…This so-called 'short-term Crabtree-effect' has been ascribed to the inability of such yeasts to instantaneously enhance their respiration rate (Petrik et al 1983;Rieger et al 1983;Kfippeli 1986). This would leave them unable to completely respire the increased flux of sugar entering the cell (and the glycolytic pathway) as a consequence of the increased extracellular sugar concentration.…”
Section: Transient State Kinetics Of Sugar Metabolismmentioning
confidence: 99%
“…The method developed by von Meyenburg (1969) involved the construction of gas balances for S. cerevisiae at a number of different dilution rates, both in the fully respiratory range of (Barford & Hall 1979;Rieger et al 1983). Furthermore, it is highly unlikely that YA'r• is constant at all growth rates, since it is well known that the protein content of S. cerevisiae increases significantly with increasing growth rate (Furukawa et al 1983;Verduyn et al 1990a;Fiechter & v o n Meyenburg 1969), both under anaerobic and aerobic conditions.…”
Section: Calculation Of P/o-ratios For Growth On Glucosementioning
confidence: 99%